PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, EQUITY SENSITIVITY TERHADAP PERILAKU ETIS MAHASISWA : (Studi Kasus Fakultas Ekonomi Dan Bisnis Program Studi S1 Manajemen Universitas Kristen Indonesia Maluku) - Maartje Paais; Margaretha R. Apituley; Thomas Aurima (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract. The research objectives are 1). To analyze the effect of emotional intelligence on student ethical behavior 2). To analyze the effect of intellectual intelligence on students' ethical behavior. 3). To analyze the effect of Equity Sensitivity on student ethical behavior 4). To analyze the effect of emotional intelligence, intellectual intelligence, and equity sensitivity simultaneously on students' ethical behavior. The population of this study were all undergraduate students at the Faculty of Economics and Business in the Management Study Program class of 2021 with a total of 75 people who were still active in the 2021/2022 Academic Year. The sample used in this study were all undergraduate students at the Faculty of Economics and Business Management Study Program class of 2021 who were still active in the 2021/2022 academic year, due to the relatively small population of 75 people, the sampling technique used in This research is a saturated sampling technique (census).